2018
DOI: 10.1111/ijfs.13848
|View full text |Cite
|
Sign up to set email alerts
|

Identification of antioxidant and anti‐inflammatory peptides obtained by simulated gastrointestinal digestion of three edible insects species (Gryllodes sigillatus, Tenebrio molitor, Schistocerca gragaria)

Abstract: The aim of this study was to determine the effect of heat treatment of edible insects on antioxidant and anti‐inflammatory activities of peptide fractions from hydrolysates obtained by in vitro gastrointestinal digestion thereof. Identification of bioactive peptides from the edible insects and their chemical synthesis were carried out as well. The highest antiradical activity against ABTS•+ and DPPH• was noted for the peptide fraction from the Gryllodes sigillatus protein preparation (EC50 value 2.75 and 6.91 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 39 publications
1
94
1
Order By: Relevance
“…Food-derived bioactive peptides with potential use as nutraceuticals and health supplement have increased interests of nutraceutical industries (S anchez & V azquez, 2017;Zieli nska et al, 2018). In spite of the significant progress in the isolation and purification of bioactive peptides from several natural sources, there are still several limitations in obtaining and purifying sufficient quantity of bioactive peptide fractions to perform the human trial at a large scale without losing activity (O'Keeffe et al, 2017;Shen & Matsui, 2017).…”
mentioning
confidence: 99%
“…Food-derived bioactive peptides with potential use as nutraceuticals and health supplement have increased interests of nutraceutical industries (S anchez & V azquez, 2017;Zieli nska et al, 2018). In spite of the significant progress in the isolation and purification of bioactive peptides from several natural sources, there are still several limitations in obtaining and purifying sufficient quantity of bioactive peptide fractions to perform the human trial at a large scale without losing activity (O'Keeffe et al, 2017;Shen & Matsui, 2017).…”
mentioning
confidence: 99%
“…However, the ABTS antioxidant capacity increased significantly. Apart from phenolics, dried lychee fruit contains many additional components (such as carbohydrates and proteins), and their interactions may adversely influence the release of bioactive phenolics as well as reduce the antioxidant efficacy (Zielińska et al ., ). Lucas‐Gonzalez et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, the ABTS antioxidant capacity increased significantly. Apart from phenolics, dried lychee fruit contains many additional components (such as carbohydrates and proteins), and their interactions may adversely influence the release of bioactive phenolics as well as reduce the antioxidant efficacy (Zieli nska et al, 2018). Lucas-Gonzalez et al (2018) researched the changes in the antioxidant potential of flours obtained from persimmon fruit after simulated digestion, and illustrated that after gastric digestion significant losses were observed, whereas after intestinal digestion their antioxidant activity increased with respect to gastric digestion and was similar to undigested samples.…”
Section: Discussionmentioning
confidence: 99%
“…() showed that β‐casein‐derived peptides, such as XPP and XP, were especially resistant to the digestive action of intestinal proteases in vivo . Many investigations are focused on the in vitro , in vivo , or ex vivo digestibility of food proteins and the bioactivity and bioavailability of peptides obtained during the enzymatic hydrolysis process (González‐Montoya et al ., ; Sanchón et al ., ; Jakubczyk et al ., ; Zielińska et al ., ; Egger et al ., ; Asledottir et al ., ; Wada & Lönnerdal, ; Karaś et al ., ). These models are suitable for evaluation of the influence of gastrointestinal digestion protein on the release of bioactive peptides or susceptibility of peptides to digestion (Minekus et al ., ; Udechukwu et al ., ).…”
Section: Digestion and Absorption Of Protein And Peptidesmentioning
confidence: 99%